Chemical constituents of the insecticidal active extract of Tinospora crispa / Nor Aziyah Bakhari, Siti Nur Amirah Diana Fadzillah and Norain Isa - Bakhari, Nor Aziyah; Fadzillah, Siti Nur Amirah Diana; Isa, Norain (Research Management Institute (RMI), 2013)
Tinospora crispa Miers (Menispermaceae) is a climbing vine with stems rich in warts. The plant is called Akar Seruntum or Patawali in Malaysia and is widely used for treating skin complaints, malaria, bacterial abscess, high blood pressure and diabetes. In the present study, the stems of T. crispa were collected from the locality and succesively extracted with petroleum ether, followed by chloroform and ethanol. The insecticidal active extract (ethanol extract) was subjected to column chromatography of silica gel eluted with a gradient mobile phase containing hexane, chloroform and ethanol. Among the chemical constituents isolated are n-tetracosyl trans-ferulate and n-octacosyl alcohol, along with three known aporphine alkaloids; N-formylnornuciferine, N-acetylnornuciferine and lysicamine. All compounds were identified by comparing their spectroscopic data (UV, IR, 1H NMR, MS) with data from corresponding values in the literature. Isolation of n-tetracosyl trans-ferulate and n-octacosyl alcohol is reported the first time for T. crispa.